Managing Employee Expectations During An Acquisition: A Case Study Approach - Pankaj Kumar, Riddhi Doshi; Avinash, V. Kothari (2010)
Over the last decade, Mergers and Acquisitions (M&A) have been viewed as a popular strategy for growth, diversification and achieving a more global presence. Despite the growing number of transactions worldwide, the rate of failure reported has been rather high. The failure has been attributed to many reasons such as leadership, communication, culture and the list goes on. During these trying times, management of the employees’ expectations is pivotal. This Management research focuses to uncover the key factors which are essential in managing employee expectations during an acquisition. The research is centered on ACons, a technical consulting firm operating within the purview of the Oil and Gas Industry that was fully acquired by AComp, a multinational company in July, 2009. A qualitative research was conducted using an interpretivist-constructivist paradigm and Grounded Theory. Semi structured in-depth interviews were utilized to elicit the experience, feeling and perceptions of the selected employees before and after the acquisition period. These findings were then used as a means to determine whether there was any breach or violation to the psychological contract of the employees. The findings revealed four key themes which were failure of human resource, lack of communication, lack of leadership and cultural mismatch. The outcomes suggest that the acquisition as a whole would have been a complete success if the key themes identified had been adhered to from the onset of the acquisition process. This would have ensured minimum impact to the employees’ psychological contract, further ensuring that it continuously remains in a “balanced” state and the acquisition process is smooth and successful.